Keragaman Morfologi, Fisiologi, Biokimia dan Virulensi Galur Xanthomonas citri sub sp. citri Penyebab Penyakit Kanker pada Jeruk - Kristi, Agusti; Mutaqin, Kikin Hamzah; Giyanto (Jurnal Fitopatologi Indonesia, 2022)
Diversity of Morphology, Physiologi, Biochemistry and Virulence of Xanthomonas citri sub sp. citri Causes Cancer in Citrus Citrus cancer is an important disease of citrus plants in the world, including Indonesia. Identification of pathogens by farmers is still based on disease symptoms, even though pathogens have a diversity of virulence, pathotypes, genetics, and host plants. The aim of the study was to determine the morphological, physiological, biochemical, molecular, and virulence diversity of citrus cancer bacteria. Bacteria isolated from samples of lemon, lime, kaffir lime, siam and fortunella which showed typical symptoms of cancer in Bogor and Kabupaten Lima Puluh Kota West Sumatra. Bacterial characteristics were carried out based on morphology, physiology, biochemistry and molecular using universal primer PCR, as well as pathogenicity in citrus cultivars lemon, lime, kaffir lime, siam, and fortunella. The results obtained 16 strains of pathogenic bacteria from samples of citrus plants that showed typical symptoms of cancer. Colonies of pathogenic bacteria vary according to colony size, color, and texture; physiologically and biochemically also varied based on the ability of protease, oxidase, casein and starch hydrolysis as well as their pathogenicity in the four citrus cultivars also varied. There were four virulent strains (LB04, NP02, PB05, and SP05) in lemon, lime, kaffir lime and siam with incubation period of 23–27 days, incidence 22.25–90.15%, and severity 15.80–78.85%. The most virulent strain LB04 based on incidence, severity, and AUDPC; lime cultivars are the most susceptible. Based on the nucleotide analysis of the 16S rRNA gene, the PB01 strain was confirmed as Xanthomonas citri subsp. citri (MK121207.1) with 99.7% homology so that it is included in pathotype A (Asiatic).